Diethyl 4-(4-ethoxyphenyl)-2,6-dimethyl-1,4-dihydropyridine-3,5-dicarboxylate - Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title compound, C(21)H(27)NO(5), the dihydropyridine ring adopts a boat conformation. The ethoxyphenyl ring is oriented approximately perpendicular to the planar part of the dihydropyridine ring, making a dihedral angle of 89.45 (6)°. An intramolecular C—H⋯O hydrogen bond generates an S(6) ring motif. In the crystal structure, neighbouring molecules are linked into chains along the a axis by N—H⋯O hydrogen bonds and the chains are interconnected into two-dimensional networks parallel to the ab plane by C—H⋯O hydrogen bonds. The structure is further stabilized by weak C—H⋯π interactions.